Ελληνικές μορφές - Αρτεμάκης, Στέλιος Ι., 1928-
Παπαρηγόπουλος Κωνσταντίνος -- Παπαδιαμάντης Αλέξανδρος -- Αλέξανδρος Μωραϊτίδης -- Νίκος Καζαντζάκης -- Κόντογλου Φώτης -- Καρκαβίτσας Ανδρέας -- Στρατής Μυριβήλης -- Κώστας Ουράνης -- Ανδρέας Κάλβος